Thesaurus of traditional English metaphors - Wilkinson, P. R. (Peter Richard), 1926- (Routledge, 2002)
"Metaphors are taken to include a variety of figurative meanings such as similes, proverbs, idioms, slang and catchphrases, though literary metaphors are avoided. The author draws particularly on his extensive contact with the rural cultures of Yorkshire, Lancashire, Dorset and Cornwall. Expressions from Scotland, North America, Australia and other parts of the English-speaking world are also included. The book thus provides an overview of folklore and folk wisdom as reflected in figurative expressions."--Jacket